IoT in Patient Respiratory Condition & Oxygen Regulator's Flowrate Monitor - Ayu Jati Puspitasari; Arya Nicosa; Dian Bayu Prakarsa; Djiwo Harsono (IAES Indonesia Section, 2020)
Respiratory condition monitoring, including respiration rate and oxygen saturation, and oxygen flowrate in oxygen tanks needed for patients undergoing oxygen therapy. Lack of medical staff in hospitals and efforts to minimize interactions between patients and nurses during the pandemic, open opportunity to develop the respiratory condition and oxygen flowrate monitoring systems using the Internet of Things (IoT) technology. Respiration rate and oxygen saturation data send to the local web network using the ESP8266 WiFi module and router. This monitoring system website was built on a server computer in the monitoring room using the PHP-MySQL programming language with Sublime Text 3 and XAMPP software. The website consists of features of the new user registration, user login, adding patient data, editing patient data, searching for patients, and patient respiratory condition monitoring pages. Connection speed based on the ability of the router range and the distance between the router and the microcontroller. For testing the reliability of the connection, the system simulated interrupted. The reconnecting times for the router and microcontroller range 3, 5, and 7 meters are 35.4 s, 35.6 s, and 35.3 s, respectively. The average response time for the system to receive data from the microcontroller and display the data on the monitoring page is 1.998 s, and there is no different data from the data on the web database and data on the serial monitor.